B/ordering space - van Houtum, Henk; Kramsch, Olivier; Zierhofer, Wolfgang (Oxon : Routledge, 2016)
"In the wake of globalization, numerous social scientists are turning to concepts of mobility, fluidity and hybridity to characterize a presumed de-territorialization and de-bordering of contemporary social and economic relations. This book brings together a select group of internationally renowned human geographers to explore the use of these concepts in relation to space, place and territory. In doing so, they (re)situate the subject of borders as active socio-spatial processes from a variety of theoretical perspectives. The contributors link debates on borders to discussions within the wider sphere of cultural studies, notably those addressing themes of migration, post-colonialism, the formation of national/regional identities and radical democratic practice. The chapters focus on those discursive practices that constitute 'bordered' geographical entities in the first instance through differentiated regimes of discourse. The book thus transcends the narrower field of borderlands research by building bridges to other domains of enquiry within political and human geography."--
Keywords: Geographical perception; Human territoriality; Globalization--Social aspects